2014
DOI: 10.1088/1757-899x/61/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Melting points and chemical bonding properties of 3d transition metal elements

Abstract: Abstract. The melting points of 3d transition metal elements show an unusual local minimal peak at manganese across Period 4 in the periodic table. The chemical bonding properties of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel and copper are investigated by the DV-X cluster method. The melting points are found to correlate with the bond overlap populations. The chemical bonding nature therefore appears to be the primary factor governing the melting points. IntroductionIn general, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In our investigation, for ZnO/CP_RT is reported narrowing d-spacing with crystallite size 20 nm, and for ZnO/CP_120 is reported non-uniform strain with the large crystallites size 27 nm. Meanwhile, the other composites show the uniform strain with narrowing d-spacing of ZnO/CP_10, ZnO/CP_90, and ZnO/CP_240 for crystallite size 16 nm, 20 nm, and 25 nm, respectively, this phenomenon is strongly influenced by the overlaping of neighboring atoms which can contribute to the strain formation [47,48]. Comparison of crystallite size to pure ZnO from previous studies is also reported to determine the changes that occur as an effect…”
Section: Resultsmentioning
confidence: 96%
“…In our investigation, for ZnO/CP_RT is reported narrowing d-spacing with crystallite size 20 nm, and for ZnO/CP_120 is reported non-uniform strain with the large crystallites size 27 nm. Meanwhile, the other composites show the uniform strain with narrowing d-spacing of ZnO/CP_10, ZnO/CP_90, and ZnO/CP_240 for crystallite size 16 nm, 20 nm, and 25 nm, respectively, this phenomenon is strongly influenced by the overlaping of neighboring atoms which can contribute to the strain formation [47,48]. Comparison of crystallite size to pure ZnO from previous studies is also reported to determine the changes that occur as an effect…”
Section: Resultsmentioning
confidence: 96%
“…The bond length model uses the formula of the compound (encapsulating information about the type of compound, e.g., ionic, Zintl phases, or intermetallic) as well as the composition of the two atomic sites (encapsulating information about chemistry, deficiency, and mixing) as inputs and predicts the most likely nearest neighbor distance. The site compositions and formula are represented using chemical descriptors (e.g., electronegativity, number of valence electrons, or position on the periodic table) available on the Citrination platform. A heuristic bond length estimate generated by summing the average atomic radii for the sites was also calculated as an additional descriptor. Machine learning and data mining algorithms are significant steps forward for the current single-crystal-based approach, compared to previous automated crystal structure solutions, for example, determining structures from powder diffraction data in a hybrid density functional theory (DFT) experimental way …”
Section: Resultsmentioning
confidence: 99%
“…Another possible cause of such difference can originate from the lack of electron effects. It was shown on the example of 3d transition metals that chemical bonding nature, in particular, bond overlap population, has a signi cant in uence on melting points [48]. However, a detailed investigation of reasons underlying the calculated melting points' overestimation is beyond the scope of this paper.…”
Section: Thermal Expansion and Melting Pointmentioning
confidence: 93%